Earth Observation by GNSS and GIS Techniques (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint highlights recent advances in the integration of Geographic Information Systems (GIS) and Global Navigation Satellite Systems (GNSS) for Earth observation and geospatial research. Over the past decades, these technologies have evolved significantly, becoming essential tools for positioning, navigation, and environmental monitoring. The Special Issue brings together eight high-quality research articles that span diverse themes, including vegetation monitoring, rockfall modeling, coastal and wetland mapping, geoid computation, landform erosion, open-ocean and inland water monitoring, and deformation assessment. By integrating remote sensing data (satellite imagery, UAV photogrammetry, SAR), GNSS measurements, and advanced GIS-based processing, the featured studies highlight new methodological approaches for monitoring natural hazards, tracking environmental changes, and improving our understanding of the Earth’s processes. Overall, this Reprint emphasizes the interdisciplinary nature of modern geospatial research and the critical role played by GIS and GNSS in advancing our understanding of our planet’s dynamic systems.